Potential of Moringa oleifera as an Antibacterial and Antibiofilms in Root Canal & Tooth Surface Disease Empirical, In Vitro & In Silico - Meiny Faudah Amin; Taufiq Ariwibowo; Salsabila Aqila Putri; Dikdik Kurnia (Scientific Dental Journal, 2024)
Moringa oleifera is one of the typical plant in Southeast Asia, especially Indonesia. Moringa leaves are known as plants containing bioactive compounds with multiple activities. Polyphenol, quercetin, tannin, and saponin compounds in Moringa leaves have anti-inflammatory, antidiabetic, and antibacterial activities. The potential of Moringa leaf extracts as an antibacterial need to be tested in silico and in vitro to determine the suitability of specific bioactive compounds. The aim is to know the potential of Moringa oleifera leaves as antibacterial, antibiofilm in root canal disease and tooth surfaces. This research method is an empirical study, In vitro and In silico.